Building Educational Quality Through Personnel Management: Case Study at MIN 3 Kebumen - Supriyanto, Dwi; Maryanto, Maryanto; Kurniawan, Benny; Rinawati, Atim; Fauziah, Muna (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze personnel management to build the quality of education at MIN 3 Kebumen. This study uses a qualitative approach with a case study type. Data collection was obtained through observation, in-depth interviews, and documentation. Data were analyzed through data reduction, data presentation, verification, and concluding. Checking the validity of the data through credibility testing (internal validity) with extended observation, increased persistence and triangulation; transferability (external validity); dependability (reliability); and confirmability (objectivity). The quality of MIN 3 Kebumen has been built with personnel management as evidenced by the fulfillment of personnel management steps including planning, organizing, actuating, observing, procuring workers, developing, compensating, integrating, maintaining, and separating.